THE PRESENCE OF ENDOGENOUS PYROGEN IN NORMAL RABBIT TISSUES - Snell, E. S. (The Rockefeller University Press, 1965)
Saline extracts of homogenized, uninfected, rabbit tissues produced febrile responses when injected intravenously into rabbits. Extracts of muscle, lung, and heart evoked fevers that were similar to those induced by leucocyte pyrogen; extracts of spleen, liver, and kidney caused more sustained fevers. The minimal pyrogenic dose appeared to be between 1.5 and 3 gm wet weight of tissue. Evidence is presented that neither Gram-negative bacterial endotoxin nor polymorphonuclear leucocytes (circulating or sequestered in the tissues) can be implicated as the source of pyrogen in tissue extracts. It seems likely, therefore, that a pyrogenic material of truly endogenous origin is widely distributed in tissues. Tissue pyrogen appears to be a large molecule which is relatively resistant to treatment with acid but not with alkali. Possible pathological roles for this endogenous agent (or agents) are briefly indicated.